Severe chest and back pain due to extra-pulmonary emphysema above 5,000 m: a series of case reports - Gan, Zhixin; Wu, Jialin; Tian, Jingdu; Han, Xiaoli; Yang, Qian; Zhang, Lei; Yang, Xi; Han, Xiaobo (Frontiers in Medicine, 2025)
BackgroundExtra-pulmonary emphysema is characterized by the presence of gas within loose soft tissues outside the lungs. This condition is frequently mistaken for acute cardiovascular diseases, leading to potential misdiagnosis. Enhancing clinical recognition of extra-pulmonary emphysema is critical for improving patient outcomes at high altitude. Notably, hyperbaric oxygen therapy has shown promise as a treatment modality for this condition.ObjectTo evaluate the feasibility of early detection and hyperbaric oxygen therapy for extra-pulmonary emphysema in high-altitude regions.MethodA retrospective analysis was conducted on non-trauma patients presenting with chest and back pain in areas exceeding 5,000 meters in altitude from May to December 2024. Patients with a confirmed diagnosis of extra-pulmonary emphysema based on computed tomography (CT) imaging were included. Clinical data and treatment details were collected, and prognostic outcomes were monitored.ResultsNine young male patients, averaging 23.56 ± 5.27 years, presented with symptoms of neck and chest pain. None had a history of chronic disease, surgery, or trauma. Initial misdiagnosis occurred in seven cases, with only two correctly identified as simple extra-pulmonary emphysema. Eight patients showed significantly improvement following hyperbaric oxygen therapy at 2.0 atmospheres absolute (ATA).ConclusionRecognizing extra-pulmonary emphysema at high altitude is crucial, especially severe mediastinal emphysema. Hyperbaric oxygen therapy may serve as an effective treatment option for this condition.